Love your mistakes! - They help you adapt to change: The new scale of learning culture - Wioleta Kucharska; Denise A. D. Bedford (Gdańsk University of Technology, Faculty of Management and Economics, 2019)
Purpose: There is no learning without making mistakes. Collaboration, knowledge, and learning culture shape organizational behaviors. Hence, this study aims to develop a theoretical model of the above constructs to determine how mistakes are related to organizational intelligence based on the structural model, including the relations between the above constructs. Methodology: New scales of the above constructs, including the learning culture scale, which is composed of the dimensions of "acceptance of mistakes" and "learning climate," were developed and validated based on two samples: students aged 18-24 and employees aged >24 who work in knowledge-driven organizations. Structural equation models were then developed, assessed, and compared. Findings: Mediated by "acceptance by mistakes," the effect of the "learning climate" on "change adaptability" has been detected for young students aged 18-24 but this relation is not significant for business employees aged >24. Limitations: Both samples were obtained from Poland, and "business sample" is in majority represented by small- and medium-sized companies. Hence, the business sample may reflect national culture. Big companies, more mature, usually design their own culture fitted to their business aims. Therefore, this study can be replicated for big Polish companies, international companies located in Poland and, for other countries. Practical implications: Acceptance of mistakes is vital for learning culture development. Mistakes help employees adapt to change. Hence, a learning culture that excludes the acceptance of mistakes is somehow artificial and may be unproductive. Paradoxically, the fact that employee intelligence (change adaptability) is increasing via mistakes does not mean that organizational intelligence is increasing. It suggests that Polish knowledge organizations are not learning organizations. Scientific implications: In this study, mistakes are presented as a precious resource that enables the adaptation and development of intelligence. Hence, this study opens a new area of research in the "management of organizational mistakes." Novelty: This study breaks with the convention of "excellence" and promotes the acceptance of mistakes in organizations to develop organizational intelligence. This study is also the first to propose a constant learning culture scale that embodies the acceptance of mistakes and "learning climate." Further, it empirically proves the value of mistakes.
Keywords: D83; M14; 330; organizational learning; change adaptability; constant learning culture; knowledge culture; collaborative culture